Analysis of the Operational Cost Budget as a Tool for Planning and Controlling Operational Costs at the Regional Water Company of Donggala Regency - Dewi Sinta; Rajindra Rajindra; Guasmin Guasmin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
The purpose of this research is to find out and analyze the procedure/mechanism of budgeting and the causes of the difference (variance) between the budget and the realization of operational costs that the PDAM of Donggala Regency has determined. The research method used is the descriptive analysis method and analysis of variance. The analysis of variance shows that in 2015 the total operating costs occurred unfavorable deviations with the percentage of -1.96%. In 2016 the total operational costs occurred unfavorable deviations with the percentage of -5.41%. In 2017 the total operational cost deviation occurred favorable with the percentage of 14.38%. In 2018 z total operating costs occurred deviations favorable with the percentage of 14.45%. In 2019 the total operational costs occurred deviation favorable with the percentage of 24.6%. Based on the analysis results that the deviations that occur between the budget and the realization of operational costs are still within the control limits, management can anticipate that the realization does not deviate far from the budget that has been set.